2008
DOI: 10.1038/cgt.2008.90
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy with radiation or cisplatin enhances the potency of Ad5/35 chimeric oncolytic adenovirus in a preclinical model of head and neck cancer

Abstract: Ad5/35 chimeric oncolytic viruses (OVs) have earlier been shown to increase the level of vector transduction, intratumoral virus spread and survival in a number of xenograft models when compared with Ad5-based viruses. Because radiation and chemotherapy are the current standards of care for most cancer indications, Ad5/35 OVs have been tested here in combination with either radiation or chemotherapy in a head and neck cancer (HNC) xenograft model to determine whether such combination therapies enhance the pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 17 publications
(40 reference statements)
0
18
0
Order By: Relevance
“…These findings are in line with the literature. Both cisplatin and radiation have been shown to reduce body weight [54-57]. Further, chemotherapy treatment can suppress voluntary activity, including decreased running wheel [17, 58-61] and open field activity [56, 57].…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in line with the literature. Both cisplatin and radiation have been shown to reduce body weight [54-57]. Further, chemotherapy treatment can suppress voluntary activity, including decreased running wheel [17, 58-61] and open field activity [56, 57].…”
Section: Discussionmentioning
confidence: 99%
“…This presents another physical barrier obstructing the movement of the relatively large viral particles between cells. As mentioned previously, several studies have shown that a combination of apoptosisinducing drugs and oncolytic therapy results in increased viral spread within tumors and a synergistic antitumor effect (Raki et al, 2005;reviewed in Mi et al, 2001;Yun, 2008;Ganesh et al, 2009). This may be due, at least in part, to the increased viral release and the formation of apoptotic bodies, but may also be attributed to the increase in interstitial space created by the apoptotic cells.…”
Section: Densely Packed Tumor Cellsmentioning
confidence: 92%
“…The synergistic effects of apoptosis-inducing drugs and viral therapy have been well documented (Raki et al, 2005;reviewed in Mi et al, 2001;Yun, 2008;Ganesh et al, 2009). In addition, adenoviruses with mutated E1B-19kD, a gene that inhibits apoptosis, have increased antitumor efficacy compared with E1B-19kD competent viruses (Sauthoff et al, 2000;Kim et al, 2002;Yoon et al, 2006).…”
Section: Viral Production and Releasementioning
confidence: 93%
“…The most studied regimens consist of OVs in combination with chemotherapeutic agents, including 5-fluorouracil [87], cisplatin [88], oxaliplatin [37], gemcitabine [89], temozolomide [90] and taxanes (e.g., docetaxel and paclitaxel) [91,92]. Cooperation with radiotherapy has also been described [88].…”
Section: Combining Oncolytic Viruses and Standard Therapiesmentioning
confidence: 99%